Hereditary features of plasma concentrations of endothelin-1 in men with hypertension and chronic heart failure - H. O. Palahniuk; V. M. Zhebel (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
Objective. To improve diagnosis of the severity of essential hypertension in men by determining the plasma levels of ET-1 in patients with different ET-1 gene variants.